MRSA bacteraemia complicating amphotericin B treatment of cryptococcal meningitis - J Scriven; J Cirota; C Viljoen; M Black; G Meintjes (Southern African Journal of HIV Medicine, 2013)
Intravenous amphotericin B is a key component of the antifungal therapy for cryptococcal meningitis recommended in South African and international guidelines. Unfortunately, its use is associated with significant toxicity including deterioration in renal function, electrolyte disturbance, anaemia and infusion reactions. Chemical phlebitis is common following administration via peripheral cannulae. This can be complicated by bacterial infection, resulting in localised cellulitis or bacterial sepsis. Here we describe two patients with cryptococcal meningitis who developed methicillin-resistant Staphylococcus aureus (MRSA) bacteraemia during, or shortly after treatment with amphotericin B. These cases illustrate the dangers of line-related sepsis in hospitalised individuals and some of the difficulties encountered during treatment of this condition.